Finite-time control for interval type-2 fuzzy time-delay systems with norm-bounded uncertainties and limited communication capacity - Zhao, Tao; Liu, Jiahao; Dian, Songyi (Information sciences, 2019)
This paper investigates the finite-time stabilization problem for interval type-2 T-S fuzzy systems with norm-bounded uncertainties and time-varying delays. A static output feedback controller is designed to guarantee the finite-time stability of closed-loop fuzzy control systems. Data packet loss is assumed to exist in the feedback transmission channel, and a novel delay product-type Lyapunov–Krasovskii function is constructed for deriving the delay-dependent stabilization conditions. These conditions can be denoted by linear matrix inequalities, according to matrix decoupling techniques and inequality constriction methods. The information of the upper and lower membership functions is integrated into the stabilization conditions using a membership function-dependent analysis method to reduce conservativeness. The simulation results demonstrate the effectiveness of the proposed finite-time control method.